Thermal decomposition of fire-retarded high-impact polystyrene and high-impact polystyrene/ethylene–vinyl acetate blend nanocomposites followed by thermal analysis. (April 2014) - Katančić, Zvonimir; Travaš-Sejdić, Jadranka; Hrnjak-Murgić, Zlata; Jelenčić, Jasenka
Blend nanocomposites of high-impact polystyrene and ethylene–vinyl acetate at a ratio of 3:1, with the addition of aluminum hydroxide Al(OH)3 and diphenyl 2-ethylhexyl phosphate (DPO) as fire retardants (FRs) and silica (SiO2 ) nanofiller were prepared by extrusion. Thermal decomposition, mechanism and kinetics of degradation of the studied samples were characterized by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The fire-retarded samples were characterized by following the degradation kinetics obtained from TGA data by recording the samples at four different heating rates. That enables us to determine one of the kinetic parameters, activation energy ( E a ) of thermal decomposition. The effect of high concentration of FRs on morphology and properties of the studied samples were analyzed by scanning electron microscopy and mechanical properties. The obtained results show that the FRs delay thermal decomposition, particularly in combination with SiO2 nanofiller, which significantly contributes to slowing down the degradation process.